The spatial cognition of Mediterranean in Slovenia - Staut, Miha (Acta geographica Slovenica, 2007)
On the basis of a previously tested method, the cognition of the spatial extent of the Mediterranean in Slovenia is presented. The Mediterranean may be determined on the basis of numerous and very diverse criteria. It is therefore a very subjectively determined notion, where geographical and non-geographical definitions can be treated as equivalent. The research made use of a questionnaire method, which revealed the opinions of the inhabitants living in the area, generally regarded as being Mediterranean. The determination of the Mediterranean was achieved with the aid of a special question. Respondents were asked to graphically delineate its border in Slovenia on a specially prepared general map included in the questionnaire on the basis of their subjective complex perception of the characteristics by them understood as Mediterranean. The questionnaire was spatially structured by the following regions: Slovene Istria, the Vipava Valley, the Vipava Hills,the Goriška ravan, the Brda Hills, the Kras, the Pivka Basin, the Reka Valley, the Brkini Hills and the Matarsko podolje and Ljubljana with its surroundings. By drawing on the fuzzy logic theory and helped by computer techniques all the answers were merged on a special map showing the extent and membership of the fuzzy set "Mediterranean" within the crisp set "Slovenia". The border between the Mediterranean and non-Mediterranean part of Slovenia is in this way established as a continuous transition. The mean value of this transition goes from Šempeter, passes the eastern flank of Karst, beside Divača and ends on the eastern side of Slavnik. A more restrictive criterion of the membership function value of 0.95, includes in the Slovenian Mediterranean only the sea and its most immediate hinterland. Particularly interesting proved differences in the spatial cognition of the Mediterranean's borders in Slovenia between different survey regions.
Keywords: Slovenia; Slovenija; Mediterranean Basin; Sredozemlje; Slovensko Primorje; slovenska Istra; Slovenian Istria; prostor; regionalna identiteta; kulturna antropologija